1979
DOI: 10.1002/ijc.2910230120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corynebacterium parvum on hemopoietic stem‐cell kinetics

Abstract: The intravenous administration of 548 microgram of killed Corynebacterium parvum (C. parvum) into C57BL mice leads to a significant decrease in the number of bone-marrow colony-forming-units in spleen (CFUs) as early as 12 h after the injection of the bacterium. This decrease persisted in varying degrees for 3 weeks. After an initial fall at 24 h, the splenic CFUs exhibited a rapid expansion and reached values 10 times higher than the control range on the ninth day. A significant rise in the number of circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Three potential sites exist for the anti-turnout actions of PGEs. Systemic Corynebacterium parvum is thought to exert its non-specific anti-tumour effect by increasing the output of mononuclear phagocytes from the marrow [6,10,12,42] and/or by activating macrophages [3,17], and NK cells via interferon [1,2,40]. Systemic Corynebacterium parvum is thought to exert its non-specific anti-tumour effect by increasing the output of mononuclear phagocytes from the marrow [6,10,12,42] and/or by activating macrophages [3,17], and NK cells via interferon [1,2,40].…”
Section: Introductionmentioning
confidence: 99%
“…Three potential sites exist for the anti-turnout actions of PGEs. Systemic Corynebacterium parvum is thought to exert its non-specific anti-tumour effect by increasing the output of mononuclear phagocytes from the marrow [6,10,12,42] and/or by activating macrophages [3,17], and NK cells via interferon [1,2,40]. Systemic Corynebacterium parvum is thought to exert its non-specific anti-tumour effect by increasing the output of mononuclear phagocytes from the marrow [6,10,12,42] and/or by activating macrophages [3,17], and NK cells via interferon [1,2,40].…”
Section: Introductionmentioning
confidence: 99%
“…After SC injection the nearest lymph node becomes labelled and when C. parvum is injected intratumorally (IT) it remains there for as long as 15 days [29]. It has been found that soon after C. parvum injection, macrophages infiltrate the lymphoid organs and the liver [4,5] Data provided by Scott et al [29] demonstrated that the peritoneal and bone marrow cells are able to take up C. parvum quite readily when it is injected IP or IV. Moore et al [18] have shown that tumours are invaded by mononuclear phagocytic cells to a greater or lesser extent, depending on the immunogenicity of the tumour.…”
Section: Reprint Requests Should Be Addressed To: V Riveros-morenomentioning
confidence: 97%
“…Χημικώς είναι γλυκοπρωτεϊνες και μέχρι τώρα έχουν απομονωθεί σέ υλικό από ανθρώπινα λευκοκύτταρα τέσσερις παράγοντες μέ Μ.Β.1300, 14.700, 36.500 καί 93.000 daltons (Price et al 1975), ένώ σέ υλικό πού παρασκευάσθηκε από εμβρυϊκό πλακούντα απομονώθηκε ένας μόνο παράγοντας μέ Μ.Β. περίπου 30.000 daltons (Burgess et al 19773 (Shah et al 1978, Singer et al 1978, Eliopoulos et al 1979, Giannoulis et a 1 .1981,Reizenstein 1982.…”
Section: ρυθμιστικοί παράγοντες αίμοποίησηςunclassified